An insight into the origin, distribution, and techniques of demonstration of Langerhans cells - Sarangi Snehanjan; Aich Ritesh (Wolters Kluwer Medknow Publications, 2017)
Langerhans cells (LCs), first described by Paul Langerhans, a German physician in 1868, are dendritic cells predominantly observed in the suprabasal layers of the epidermis and the oral epithelium. These cells belong to the nonkeratinocytic population and lack desmosomal attachments to surrounding cells; thereby appearing as clear cells in histologic sections. Ultrastructurally, the cells are characterized by unique rodshaped Birbeck granules. These cells are endowed with the essential functions of foreign antigen recognition, trapping, and processing. Herein, we have concisely discussed regarding the origin, distribution, and techniques of demonstration of LCs.